Albumin removal from human serum using surface nanopockets on silica-coated magnetic nanoparticles. Issue 66 (3rd August 2017) - Bhakta, Snehasis; Dixit, Chandra K.; Bist, Itti; Macharia, John; Shen, Min; Kadimisetty, Karteek; He, Junkai; Dutta, Biswanath; Suib, Steven L.; Rusling, James F.
Abstract : Polymerized films synthesized on magnetic nanoparticles (NP) using amino acid-like monomers yielded reusable NPs that efficiently remove HSA from serum. Abstract : Selective removal of albumin from human serum is an essential step prior to proteomic analyses, especially when using mass spectrometry. Here we report stable synthetic nanopockets on magnetic nanoparticle surfaces that bind to human serum albumin (HSA) with high affinity and specificity. The nanopockets are created by templating HSA on 200 nm silica-coated paramagnetic nanoparticles using polymer layers made using 4 organo-silane monomers. These monomers have amino acid-like side chains providing hydrophobic, hydrophilic and H-bonding interactions that closely mimic features of binding sites on antibodies. The binding capacity of the material was 21 mg HSA g −1, and consistently removed ∼88% albumin from human serum in multiple repeated use.